Changes in Body Composition Using Deuterium Dilution Technique Among Young Children Receiving Specialized Nutritious Foods for Moderate Acute Malnutrition in Sierra Leone (P10-141-19). (13th June 2019) - Suri, Devika; Potani, Isabel; Singh, Akriti; Griswold, Stacy; Wong, William; Langlois, Breanne; Shen, Ye; Chui, Kenneth; Walton, Shelley; Rosenberg, Irwin; Rogers, Beatrice
Abstract: Objectives: To determine differential changes in children's body composition—fat-free mass (FFM) and fat mass (FM)—after 4 weeks of treatment for moderate acute malnutrition (MAM) with one of 4 four specialized nutritious foods (SNFs). Methods: This sub-study was nested within a larger cluster-randomized trial comparing the cost-effectiveness of 4 isocaloric SNFs in treating MAM among children 6–59 months in Pujehun District, Sierra Leone: Corn-Soy Blend Plus w/oil (CSB + w/oil), Super Cereal Plus w/amylase (SC + A), Corn-Soy-Whey Blend w/oil (CSWB w/oil) and Ready-to-use-Supplementary Food (RUSF). Children with mid-upper arm circumference (MUAC) ≥11.5 cm and <12.5 cm with no clinical complications were enrolled and received an SNF ration bi-weekly until they reached MUAC ≥12.5 cm or up to 12 weeks. Body composition was assessed using the deuterium dilution technique at program enrollment and after 4 weeks of treatment. Changes in weight, FM, FFM and %FFM overall and by study arm were calculated; statistical significance was determined using t-tests and ANOVA (unadjusted). Results: Among 336 subjects at enrollment, mean ± SD age was 11.8 ± 6.5 mos, weight was 6.5 ± 0.9 kg, FM was 1.3 ± 0.5 kg, FFM was 5.2 ± 0.9 kg, and %FFM was 80.4 ± 7.3. After 4 weeks of treatment, mean ± SD change in weight was 0.44 ± 0.39 kg ( P < 0.001), FM was 0.09 ± 0.60 kg ( P = 0.005), FFM was 0.35 ± 0.56 ( P < 0.001), and %FFM was 0.003 ± 8.5 (NS). Overall, weight gain consisted on average of 20.9% FM and 79.8% FFM. By study arm, mean ± SD changes in FM and FFM respectively, were: 0.12 ± 0.53 kg and 0.32 ± 0.49 kg in CSB + w/oil; 0.13 ± 0.67 kg and 0.34 ± 0.64 kg in SC + A; 0.08 ± 0.65 kg and 0.36 ± 0.57 kg in CSWB w/oil; 0.02 ± 0.49 kg and 0.39 ± 0.5 kg in RUSF. These changes were not significantly different across study arms. Conclusions: Over 4 weeks of treatment for MAM, children gained roughly 80% lean mass relative to 20% fat mass. This body composition is consistent with predicted sustainability of recovery from MAM and healthier long-term disease risk. Differential effects on body composition by type of SNF were not detected after 4 weeks of treatment in this study. Funding Sources: The Office of Food for Peace, Bureau for Democracy, Conflict, and Humanitarian Assistance, U.S. Agency for International Development.